KONSEP ORANG TUA YANG DURHAKA DALAM PERSPEKTIF ISLAM - Siti Suwaibatul Aslamiyah (Universitas Islam Lamongan, 2017)
Many are peeling many of wich explore the child’s ungodly behavior to parents, but few who explore the opposite phenomenon of the ungodly behavior of parents against their children. Children is a grace from God of Allah swt to his parents to be grateful, educated and fostered to be a good person, strong personality and ethical Islamic. While, the development of religion in children is largely determined by the education and their experience, especially during the pre-election period of expectant mothers and fathers and the first growth period from 0 to 12 years. For that, the author is moved to explore and examine (about) the concept of elderly parents in the perspective of Islam. This is the author thoroughly to know who exactly the child in his existence according to Islam? What is the rule and rule of education in family and family roles in children’s education? What are the preparations (actions) that are classified as the ungodly behavior of parens against the child? In this study shows there is an effect (impact) between the family environment (parents) on the formation of islamic character and ethics in children from an early age mainly from the factors of prospective fathers and prospective mothers so the authors get the correlation that the failure of good personality planting in early childhood will turn out to form a problematic person in his adulthood (his grow up). While the success of parents guiding their children will determine the formation of character and their morals so that the family environment conditions are crucial for the success of children in social life in their adult life later (after grow up). In this study resulted in the conclusion that there are some things that make the parents become ungodly against their children and it has been conceptualized in the holy book of the Qur’an which at least in this study collected there are 14 components of eldery behavior of the lawless to their children.